Qawaidh fiqhiyyah Sebagai Landasan Dalil Hukum Islam - Hasibuan, Mhd Saleh Hasibuan; Sinaga, Riyan Syaputra; Siahaan, M Raja; Ginting , Adrian seputro; Tambunan , Hanif Rahman (Tabayyun : Journal Of Islamic Studies, 2025)
Qawaid fiqhiyyah (rules of fiqh) have a very important role in the development of Islamic law, because they provide the basic basis for determining and applying legal arguments in various contexts. This article discusses the role of qawaid fiqhiyyah as a guide in understanding and formulating the postulates of Islamic law, as well as how they are applied in solving contemporary fiqh problems. These fiqh rules, such as